SPIRIT KI HADJAR DEWANTARA DALAM IMPLEMENTASI KURIKULUM MERDEKA - Junaedi, I Komang (Padma Sari: Jurnal Ilmu Pendidikan, 2024)
This research aims to conduct a study related to the role of Ki Hadjar Dewantara's spirit of education in Indonesia in the implementation of the Merdeka Curriculum. Ki Hadjar Dewantara is a national hero known as the Father of Indonesian Education, he is the founder of Taman Siswa who coined the concept of the Tri Center of Education, namely informal, formal and non-formal. In addition, he also came up with a concept that became a slogan for education actors, namely "ing ngarso sung tulodho, ing madyo mangunkarso, and tut wuri handayani". The concept of education emphasized by Ki Hadjar Dewantara directs education to prioritize the realization of students with character and can develop their potential through inclusive and integrated education. This is evident in the implementation of the independent curriculum, so it is deemed necessary to study the spirit of Ki Hadjar Dewantara in the implementation of the independent curriculum. This research is a qualitative research with a literature review design. The research data was obtained through various references which were then analyzed by data reduction, data presentation and conclusion drawing. The results of this study are that Ki Hadjar Dewantara's thoughts in education emphasize independence, justice, and equality, and this is important in implementing an independent curriculum. In addition, learning also requires the involvement of family and community to provide students with a broader learning experience. Ki Hadjar Dewantara's spirit is reflected in the independent curriculum which prioritizes freedom of thought, social inclusion and democratic participation. With Ki Hadjar Dewantara's educational spirit, the implementation of the independent curriculum is believed to be able to apply good learning principles. With this, Indonesia will be able to build an education system that is more relevant, sustainable, and advances the progress of the nation as a whole.